The Influence of the pH Value and the Cation Composition of Dispersion Medium on the Formation of Iron-Oxygen Structures on Steel Surface - Lavrynenko, O.M.; Netreba, S.V.; Prokopenko, V.A.; Korol, Ya.D. (Хімія, фізика та технологія поверхні, 2011)
The peculiarities of the formation of iron-oxygen structures on steel surface due to its contact with aqueous dispersion medium within a wide range of pH values and in presence of cobalt and silver have been studied by X-ray diffraction in situ. It has been shown that well crystallized cobalt- and ironcontaining spinel ferrites are formed at neutral pH value of aqueous medium. The contact of steel surface with alkaline medium results in formation of weakly crystallized iron oxyhydroxides. The structure of lepidocrocite is formed on steel surface due to its contact with acid dispersion medium in absence of metal ions such as cobalt and silver. Методом рентгенофазового аналізу in situ досліджено особливості формування залізо-кисневих структур на поверхні сталі при її контакті з водним дисперсійним середовищем у широкому діапазоні значень рН та в присутності кобальту і срібла. Показано, що добре окристалізовані структури феришпінелі – магнетиту і фериту кобальту утворюються при нейтральних значеннях рН середовища. При контакті сталі з лужним дисперсійним середовищем на поверхні у всіх випадках утворюються слабко окристалізовані оксигідроксиди заліза. Структура лепідокрокіту утворюється на поверхні сталі при її контакті з кислим дисперсійним середовищем за відсутності катіонів. Методом рентгенофазового анализа in situ исследованы особенности формирования железо-кислородных структур на поверхности стали при ее контакте с водной дисперсионной средой в широком диапазоне значений рН и в присутствии кобальта и серебра. Показано, что хорошо окристаллизованные структуры ферришпинели – магнетита и феррита кобальта формируются при нейтральных значениях рН среды. При контакте стали со щелочной дисперсионной средой на поверхности во всех случаях образуются слабо окристаллизованные оксигидроксиды железа. Структура лепидокрокита образуется на поверхности стали при ее контакте с кислой дисперсионной средой в отсутствие катионов.